Numerical Modeling of a Church Nave Wall Subjected to Differential Settlements: Soil-Structure Interaction, Time-Dependence and Sensitivity Analysis. Issue 8 (13th September 2020) - Drougkas, Anastasios; Verstrynge, Els; Szekér, Pepijn; Heirman, Gert; Bejarano-Urrego, Leidy-Elvira; Giardina, Giorgia; Van Balen, Koenraad
ABSTRACT: Historic masonry structures are particularly sensitive to differential soil settlements. These settlements may be caused by deformable soil, shallow or inadequate foundation, structural additions in the building and changes in the underground water table due to the large-scale land use change in urban areas. This paper deals with the numerical modeling of a church nave wall subjected to differential settlement caused by a combination of the above factors. The building in question, the church of Saint Jacob in Leuven, has suffered extensive damage caused by centuries-long settlement. A numerical simulation campaign is carried out in order to reproduce and interpret the cracking damage observed in the building. The numerical analyses are based on material and soil property determination, the monitoring of settlement in the church over an extended period of time and soil-structure interaction. A sensitivity study is carried out, focused on the effect of material parameters on the response in terms of settlement magnitude and crack width and extent. Soil consolidation over time is considered through an analytical approach. The numerical results are compared with the in-situ observed damage and with an analytical damage prediction model.